2011
DOI: 10.1556/mental.12.2011.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the quality of life of migraineurs and tension headache patients in connection with impulsivity, empathy, depression, and vital exhaustion

Abstract: A fájdalomszindrómák depresszióval való kapcsolata részletesen dokumentált a szakirodalomban. Az impulzivitás és az empátiás készség kevésbé vizsgált vonás. Korábbi megfigyeléseink szerint az impulzivitás a migrénes betegek többségére jellemzô, empátiás készséget pedig inkább a nôbetegek mutatnak. A Nemzetközi Fejfájás Társaság (International Headache Society) kritériumai szerint diagnosztizált 87 beteggel (40 migrénes és 47 tenziós fejfájós, átlagéletkoruk 34 év) vettük fel a Beck Depresszió Kérdôívet (BDI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…An example is the Headache Disability Inventory (HDI) (53), where the authors rationally organized items into emotional and functional subscales; in a later study by Holroyd et al the factor analysis of HDI items revealed that all items loaded on a single factor (54). Different studies may find a different underlying structure within the same instrument, as exemplified by the MSQOL, which was found to have three dimensions (avoidance, relationships and feelings) in an American study (16), and four dimensions (affective, social, energetic and life rhythms) in a Hungarian one (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example is the Headache Disability Inventory (HDI) (53), where the authors rationally organized items into emotional and functional subscales; in a later study by Holroyd et al the factor analysis of HDI items revealed that all items loaded on a single factor (54). Different studies may find a different underlying structure within the same instrument, as exemplified by the MSQOL, which was found to have three dimensions (avoidance, relationships and feelings) in an American study (16), and four dimensions (affective, social, energetic and life rhythms) in a Hungarian one (17).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the new instrument with previously developed headache-specific measures could have added further evidence about the validity of the instrument and may have yielded important data about its usability. However, due to a lack of validated Hungarian translations of headache-specific QOL instruments, this approach was not possible (the validation study of the Hungarian version of the MSQOL was only published in 2011 (17)). Although the HIT-6 has been validated in Hungarian (55), due to the small sample size (only 35 Hungarian migraineurs diagnosed by their primary care physician were studied) and to the fact that, in a strict sense, HIT-6 is not a QOL instrument, we decided not to use it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation